Construction of the Aspergillus nidulans pmtC∆hogA∆yA∆ triple deletion strain by mating and benlate inducing - Tram Thi Huynh Le; Nhan Thy Le; Tien Thi Thuy Nguyen; Duong Thi Thuy Nguyen; Dong Xuan Nguyen (Ho Chi Minh City Open University Journal of Science - Engineering and Technology)
In Aspergillus nidulans, construction of double or triple deletion strain is widely carried out to investigate genetic coordination, relation, or interaction. In this study, a fungal mutant, in which pmtC, hogA, and yA are deleted, is constructed for a recent experimental purpose. The mutation strain is screened and isolated by auxotrophic mutations from progenies of a sexual mating between the two A. nidulans fungi, pmtC∆yA∆ deletion strain and hogA∆ deletion strain. The genotype of the strain obtained from the matting is confirmed by PCR indicating that the obtained strain contains deleted hogA, both wild-type pmtC and deleted pmtC deletion. Moreover, the obtained strain forms morphology with irregular edges, abnormal growth, and derived colony, which is like general morphology of diploid strains, suggesting that the mutant is a diploid strain. As benlate is a haploidization-inducer for the diploid strain, the spores of the diploid strain are spread on media with 0.05ppm of benlate. Forming colonies performing pmtC-like characteristics, such as poor development, impaired vegetation and limited conidiation, are considered as target haploid strains and confirmed by PCR. The PCR results show that, among four isolated strains, there is only one strain showing PCR band which is approximate to pmtC knock-out gene, indicating the strain carry pmtC deletion gene. As a result, the fungal strains, namely AnTLE36.HC, is a pmtC∆hogA∆yA∆ deletion strain.